Inherited predisposition to breast/ovarian cancer : the frequency and nature of BRCA1 gene mutations in South African families - Van Rensburg, Elizabeth J. (University of Pretoria, 2013)
Dissertation (MSc (Human Genetics))--University of Pretoria, 2005.